PENGARUH KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS XI SMA NEGERI 1 MAJENE - Nursang Nursang; Murtafiah Murtafiah (PEDAMATH: Journal on Pedagogical Mathematics, 2018)
This study was an expost facto study which aimed to investigate the effect of emotional intelligence on the mathematics learning outcomes of students of Majene 1 State High School 2016-2017 school year consisting of 547 people by taking samples of 27 people who were made as respondents. From the results of questionnaires collected by respondents, the respondent's maximum emotional intelligence score was 35 and the minimum score was 20 with the mean (average) of 28.93 and a standard deviation of 3.327. While the mathematics learning outcomes of students revealed that the maximum score obtained by respondents was 90 and the minimum score was 30 with a mean (average) of 67.93 and a standard deviation of 15.990. From the results of the regression analysis testing obtained the equation Y or X is Y = -20,377 + 3,049x means that mathematics learning outcomes are influenced by emotional intelligence variables which indicate a linear relationship between two variables. While the level of the relationship between the two variables obtained r value of 0.637 and the magnitude of the percentage of the effect of free vaiabel on the dependent variable obtained r2 value of 0.402 which means the effect of variable X on variable Y is 40.2% while the rest is influenced by other factors.